The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/j.bbmt.2003.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A long-term follow-up report on allogeneic stem cell transplantation for patients with primary refractory acute myelogenous leukemia: impact of cytogenetic characteristics on transplantation outcome

Abstract: The prognosis of patients with primary refractory acute myelogenous leukemia (AML) is poor. Our initial report suggested that some patients could achieve durable remission after allogeneic stem cell transplantation (SCT). Herein, we update our initial experience and report further analysis of this group of patients to determine whether there are pre-SCT prognostic factors predictive of posttransplantation relapse and survival. We reviewed the records of 68 patients who consecutively underwent transplantation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 16 publications
3
73
1
Order By: Relevance
“…Previous studies reported OS rates of 20-30% in refractory AML using standard conditioning regimens for HCT. 21,22 In our study, the incidence of relapse at 5 years was low (32% for all patients). This is comparable with published reports in advanced AML and MDS patients, or AML patients in remission with unfavorable cytogenetics.…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies reported OS rates of 20-30% in refractory AML using standard conditioning regimens for HCT. 21,22 In our study, the incidence of relapse at 5 years was low (32% for all patients). This is comparable with published reports in advanced AML and MDS patients, or AML patients in remission with unfavorable cytogenetics.…”
Section: Discussioncontrasting
confidence: 49%
“…Older individuals with myeloid diseases also have high risk cytogenetic phenotypes and increased multidrug resistance gene expression [1][2][3]; hence they are less likely cured with chemotherapy alone. Allogeneic hematopoietic stem cell transplantation (HSCT) is potentially curative with a reported disease-free survival (DFS) of 30-50% [4][5][6][7][8][9]. In MDS, HSCT is the only therapy known to improve survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fung et al [5] reviewed the records of 68 patients who consecutively underwent transplantation at the City of Hope Cancer Center with allogeneic SCT for primary refractory AML between July 1978 and August 2000. Allogeneic SCT can cure approximately one third of patients with primary refractory AML.…”
Section: Discussionmentioning
confidence: 99%